Material Properties and Safety of Cars at Crash Tests. (2016) - Fechová, Erika; Kmec, Jozef; Vagaská, Alena; Kozak, Dražan
Abstract: This article deals with the calculations of deformation work and biomechanical limits for human organism (especially head injuries) at the frontal crash of the car into the barrier using the material properties of individual types of steel. Based on the experimental and theoretical results deformation member of the most suitable steel is proposed which protects solid parts of the construction at collisions from damaging and at the same time suitable biomechanical criteria are set.